A counterion study of a series of [Cu(P^P)(N^N)][A] compounds with bis(phosphane) and 6-methyl and 6, 6′-dimethyl-substituted 2, 2′-bipyridine ligands for light-emitting electrochemical cells. Issue 48 (10th November 2021) - Meyer, Marco; Mardegan, Lorenzo; Tordera, Daniel; Prescimone, Alessandro; Sessolo, Michele; Bolink, Henk J.; Constable, Edwin C.; Housecroft, Catherine E.
Abstract : The choice of counterion in heteroleptic copper(i ) luminophores for LECs has a critical effect on the photoluminescence quantum yields of the solid materials, and on the device figures-of-merit. Abstract : The syntheses and characterisations of a series of heteroleptic copper(i ) compounds [Cu(POP)(Mebpy)][A], [Cu(POP)(Me2 bpy)][A], [Cu(xantphos)(Mebpy)][A] and [Cu(xantphos)(Me2 bpy)][A] in which [A] − is [BF4 ] −, [PF6 ] −, [BPh4 ] − and [BAr F 4 ] − (Mebpy = 6-methyl-2, 2′-bipyridine, Me2 bpy = 6, 6′-dimethyl-2, 2′-bipyridine, POP = oxydi(2, 1-phenylene)bis(diphenylphosphane), xantphos = (9, 9-dimethyl-9 H -xanthene-4, 5-diyl)bis(diphenylphosphane), [BAr F 4 ] − = tetrakis(3, 5-bis(trifluoromethyl)phenyl)borate) are reported. Nine of the compounds have been characterised by single crystal X-ray crystallography, and the consequences of the different anions on the packing interactions in the solid state are discussed. The effects of the counterion on the photophysical properties of [Cu(POP)(N^N)][A] and [Cu(xantphos)(N^N)][A] (N^N = Mebpy and Me2 bpy) have been investigated. In the solid-state emission spectra, the highest energy emission maxima are for [Cu(xantphos)(Mebpy)][BPh4 ] and [Cu(xantphos)(Me2 bpy)][BPh4 ] ( λ emmax = 520 nm) whereas the lowest energy λ emmax values occur for [Cu(POP)(Mebpy)][PF6 ] and [Cu(POP)(Mebpy)][BPh4 ] (565 nm and 563 nm, respectively). Photoluminescence quantum yields (PLQYs) are noticeably affected by the counterion; in the [Cu(xantphos)(Me2 bpy)][A] series, solid-state PLQY values decrease from 62% for [PF6 ] −, to 44%, 35% and 27% for [BF4 ] −, [BPh4 ] − and [BAr F 4 ] −, respectively. This latter series of compounds was used as active electroluminescent materials on light-emitting electrochemical cells (LECs). The luminophores were mixed with ionic liquids (ILs) [EMIM][A] ([EMIM] + = [1-ethyl-3-methylimidazolium] + ) containing the same or different counterions than the copper(i ) complex. LECs containing [Cu(xantphos)(Me2 bpy)][BPh4 ] and [Cu(xantphos)(Me2 bpy)][BAr F 4 ] failed to turn on under the LEC operating conditions, whereas those with the smaller [PF6 ] − or [BF4 ] − counterions had rapid turn-on times and exhibited maximum luminances of 173 and 137 cd m −2 and current efficiencies of 3.5 and 2.6 cd A −1, respectively, when the IL contained the same counterion as the luminophore. Mixing the counterions ([PF6 ] − and [BF4 ] − ) of the active complex and the IL led to a reduction in all the figures of merit of the LECs.